2014
DOI: 10.1115/1.4026188
|View full text |Cite
|
Sign up to set email alerts
|

Do We Really Need “Entransy”? A Critical Assessment of a New Quantity in Heat Transfer Analysis

Abstract: Recently, a group of scientists introduced a new quantity for the analysis of heat transfer problems. They called it entransy since according to their understanding it is both, an indication of the nature of energy as well as that of the heat transfer ability. This concept is critically assessed on the background of two questions: Is entransy as an extension of the well established theory of heat transfer consistent with this classical approach? And: Is there a real need for the extension of the classical theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…They only showed their viewpoint in the second paragraph of the Introduction section, and there is no further explanation for their viewpoint or analysis or discussion on the entransy theory. The comments from Grazzini and Rocchetti [13] are just the repetition of the words from Grazzini et al [7] and Herwig [11], which have already been replied and discussed. In addition, the misused concepts in Açıkkalp's work [21] have also been pointed out in Ref.…”
Section: Negative Comments On the Entransy Theory And The Repliesmentioning
confidence: 87%
See 3 more Smart Citations
“…They only showed their viewpoint in the second paragraph of the Introduction section, and there is no further explanation for their viewpoint or analysis or discussion on the entransy theory. The comments from Grazzini and Rocchetti [13] are just the repetition of the words from Grazzini et al [7] and Herwig [11], which have already been replied and discussed. In addition, the misused concepts in Açıkkalp's work [21] have also been pointed out in Ref.…”
Section: Negative Comments On the Entransy Theory And The Repliesmentioning
confidence: 87%
“…In Ref. [13], the authors only cited the work of Grazzini et al [7] and Herwig [11], and claimed that ''entransy does not contain any new information in comparison with a classical analysis of systems using entropy''. The authors did not cite any of the papers [3,17,19,20] on the other side.…”
Section: Negative Comments On the Entransy Theory And The Repliesmentioning
confidence: 97%
See 2 more Smart Citations
“…Yet, a disturbing trend has emerged in publishing: it is to copy the original work, change a few key words (i.e., "translate"), and publish the same idea brazenly as "new" after replacing the Darcy diffusion language with thermal diffusion language (as Guo et al [47] have done). Critiques of Guo et al [47] were just published independently by seven groups of authors [48][49][50][51][52][53][54], who showed that the concept of "entransy" is false and not useful.…”
Section: Technology Evolutionmentioning
confidence: 99%